Current aspects on the management of viral uveitis in immunocompetent individuals - Pleyer U (Dove Medical Press, 2015)
Uwe Pleyer,1 Soon-Phaik Chee1–51Augenklinik, Charité– Universitätsmedizin Berlin, Campus Virchow-Klinikum, Berlin, Germany; 2Ocular Inflammation and Immunology Service, Singapore National Eye Centre, 3Singapore Eye Research Institute, 4Department of Ophthalmology, Yong Loo Lin School of Medicine, National University of Singapore, 5Duke-NUS Graduate Medical School Singapore, SingaporeAbstract: Viruses are a fundamental etiology of ocular inflammation, which may affect all structures of the organ. Advances in molecular diagnostics reveal an increasingly broader spectrum of virus-associated intraocular inflammation, including all members of the herpes family, rubella virus, and other more rare causes such as Epstein–Barr and chikungunya virus. In particular, viruses of the herpes family are important causes of anterior and posterior uveitis. Owing to their often fulminant clinical course and persistence in ocular tissues, a clear differential diagnosis between alpha- and beta-type herpes viruses is essential to guide acute and long-term treatment. Here, we review the epidemiology, clinical, and laboratory findings of virus-associated uveitis with emphasis on their therapy and management and include our own experience.Keywords: clinical trials, cytomegalovirus, herpes virus, infection, inflammation, treatment, uveitis